ANALISIS PROSES PERAWATAN MESIN DENGAN METODE TOTAL PRODUCTIVE MAINTENANCE DALAM KAITANNYA DENGAN TINGKAT DEFECT DAN BREAKDOWN YANG TINGGI PADA PT. FMI JAKARTA - Haryadi Sarjono; Edi Santoso; Endy Setiawan; Arko Pujadi (Jurnal Riset Manajemen dan Bisnis, 2009)
Quality in produced product become the important factor in manufacture industry competition this time. FMI company as the biggest producer whole wheat in world always tried in order to product quality that produced may satisfied consumer desire. Problem that faced by FMI company was the high defect that exceeding standard which have determined at May-June 2009'h production. After research has doni, founded that the root caused of mctchines which doesn't work optimally. Therefore, researcher feel important discussing system of machine treatment exist in FMI company. As for method which used in this research is Stotistical Process Control (SPC) method for process quality operation, and Total Productive Maintenance (TPilrI) method for treatment machine system. By using the method, researcher will look for value of process capability (cp and cpk) by using map conduct x - R, then look for value from overall Equipment Effectiveness (oEE) in production process Mill MNO. Researcher also will lookfor potential cause that caused the height defect and breakdown in Mill MNO by Failure Mode method, Effect and Criticality Analysis (FMECA).In the end a repair suggestion will be proposed by researcher in effortto lessen level of defect may reduce breakdown time that become problem of Mill MNO. Estimate writing of this skripsi may become a positive input for continuous improvementeffort that do by PT. FMI Jakarta.Keywords : quality, defect, map conduct i- n, Ong, breakdown, FMECA, continuous improvement